THE INFLUENCE OF PRICE DISCOUNTS, BONUS PACKS, AND IN-STORE DISPLAYS ON CONSUMER IMPULSE BUYING BEHAVIOR DECISIONS AT HYPERMART MALL PANAKKUKANG MAKASSAR - Sitti Aisyah Muthmainna K. Samma; Muhammad Asdar; Nurdjanah Hamid (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
The results of this study indicate that: (1) there is a positive influence Price discount (X )1 on Consumer Impulse Buying Behavior Decisions at Hypermart Mall Panakkukang Makassar, as evidenced by the t value of 2.595> t table 1.988 with a significance value of 0.011 <0.05; and regression coefficient of 0 .400. (2) there is a positive influence of Bonus pack (X2 ) on Consumer Impulse Buying Behavior Decisions at Hypermart Mall Panakkukang Makassar, evidenced by the value of t count of 2.186> t table 1.988 with a significance value of 0.031 <0.05 ; and a regression coefficient of 0.273. (3) There is a positive effect of In-store display (X3 ) on Consumer Impulse Buying Behavior Decisions at Hypermart Mall Panakkukang Makassar, as evidenced by the t value of 2.763> t table 1.988 and a significance value of 0.007 <0.05; and a regression coefficient of 0.479. (4) Price discount (X1 ) Bonus pack (X2 ) and In-store display (X )3 together have a positive effect on Consumer Impulse Buying Behavior Decisions at Hypermart Mall Panakkukang Makassar, evidenced by the calculated f value of 17.067> f table of 2.70 and a significance value of 0.000 <0.05. (5) In-store display variable (X3 ) is the variable that has the most dominant influence, as evidenced by its regression coefficient value of 0.479.